Factors Affecting Nurse Retention in A Private Healthcare System in Malaysia - Zarin Ikmal Zan Mohd Zain; Annamma Kunjukunju; Goventhamma Subramaniam; Nur Izzana Tajuddin (Jurnal Keperawatan Indonesia, 2025)
Nurse retention has become increasingly challenging in the post-pandemic era, particularly for private hospitals. This study aimed to identify the significant predictors of nurse retention in selected private hospitals in Malaysia. A quantitative, descriptive, cross-sectional design was employed. A pre-validated, self-administered questionnaire, distributed via Google Forms, was used for data collection. The respondents included 532 registered nurses employed at three private hospitals in Malaysia. Data analysis was conducted using descriptive statistics and correlation studies, including Spearman’s rho and multiple regression analysis. Among the participants, 54% reported good job satisfaction, 27.37% expressed organizational commitment, 25.97% were satisfied with human resource practices, and 48.41% intended to remain with their current organization. The findings revealed a strong positive correlation between nurse retention, organizational commitment, human resource practices, and job satisfaction. Multiple regression analysis indicated that job satisfaction was the most significant predictor of nurse retention (F (1) = 285.334, p (.000) < .05, R2 = 0.354), followed by human resource practices and organizational commitment. These results suggest that job satisfaction is the primary factor influencing nurse retention in private healthcare settings. Therefore, hospitals must implement strategies to enhance employees’ job satisfaction. Human resource management must also establish clear policies on remuneration, career development, and employee promotion to improve nurse retention.  Keywords: intent to leave, job satisfaction, nurses, nurse retention, organizational commitment, quality of care   Abstrak Faktor-Faktor yang Memengaruhi Retensi Perawat dalam Sistem Layanan Kesehatan Swasta di Malaysia. Retensi perawat menjadi hal yang semakin menantang di pasca pandemi, khususnya di rumah sakit swasta. Studi ini bertujuan untuk mengidentifikasi prediktor signifikan retensi perawat di rumah sakit swasta terpilih di Malaysia. Desain penelitian yang digunakan adalah deskriptif kuantitatif, cross-sectional. Alat pengumpulan data yang digunakan adalah kuesioner yang telah divalidasi sebelumnya, didistribusikan melalui Google Forms untuk dikerjakan secara mandiri oleh responden. Responden terdiri dari 532 perawat terdaftar yang bekerja di tiga rumah sakit swasta di Malaysia. Analisis data menggunakan statistik deskriptif dan studi korelasi, yaitu Spearman's rho dan analisis regresi berganda. Ditemukan sebanyak 54% melaporkan kepuasan kerja yang baik, 27,37% menyatakan komitmen organisasi, 25,97% puas dengan praktik kepegawaian yang ditetapkan, dan 48,41% berkomitmen untuk tetap bekerja di organisasi mereka saat ini. Temuan tersebut mengungkapkan korelasi positif yang kuat antara retensi perawat, komitmen organisasi, praktik sumber daya manusia, dan kepuasan kerja. Analisis regresi berganda menunjukkan bahwa kepuasan kerja merupakan prediktor paling signifikan terhadap retensi perawat (F (1) = 285,334, p (.000) < .05, R2 = 0,354), diikuti oleh praktik sumber daya manusia dan komitmen organisasi. Hasil ini menunjukkan bahwa kepuasan kerja merupakan faktor utama yang memengaruhi retensi perawat di lingkungan layanan kesehatan swasta. Oleh karena itu, rumah sakit harus menerapkan strategi untuk meningkatkan kepuasan kerja karyawannya. Manajemen sumber daya manusia juga harus menetapkan kebijakan yang jelas tentang remunerasi, pengembangan karir, dan promosi jabatan untuk meningkatkan retensi perawat. Kata Kunci: keinginan untuk mengundurkan diri, kepuasan pekerjaan, komitmen organisasi, kualitas perawatan, perawat, retensi perawat